PENGARUH FAKTOR PRODUKSI TERHADAP PENGEMBANGAN PERIKANAN TUNA DI KOTA AMBON - Sangadji, Selfi; Mustaruddin, Mustaruddin; Wisudo, Sugeng Hari (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The purpose of the study is to analyze the influence level of the production factors to development of the tuna fishing industry in Ambon City. The data collected are the vessel size, gear size, long trip, fuel use, ice use, fresh water and the number of crew. The data comes from Ambon tuna fishermen. Data collected are primary and secondary data. The analysis used is multiple regression analysis. Multiple regression analysis of the relationship of tuna production gets the value of significance (sig) 0,000. Sig be in the range of beliefs